The Implementation of Partnership Program in Gresik Regency Based on Governance Perspective (Case Study in PT Petrokimia Gresik) - Wati, Susilo (Jurnal Administrasi Publik, 2013)
Governance concept offers interaction between three main actors in policy implementation, the actor are government, and society and private known as the iron triangle. This journal will discuss three actors synergies in the implementation of partnership programs conducted by PT Petrokimia Gresik in developing small enterprises in Gresik regency based on governance perspective. Based on the conducted research, the findings showed good synergy between the private (PT Petrokimia Gresik) and the community (partner member) in the implementation of the partnership program, unfortunately the synergy with government was less maximum, particularly with the Department of Cooperatives, Small and Medium Enterprises, Industry and Trade in Gresik regency this is caused by some reasons, so at the end of this journal researcher give recommendations as alternative to address the existing problems. Keywords: governance, synergy, partnership program